Аспекты финансирования развития инфраструктуры крупного промышленного города - Богачев, С.В. (Економіка промисловості, 2016)
Рассмотрены вопросы финансирования проектов и программ развития инфраструктуры крупного промышленного города. Обоснована необходимость расширения источников финансирования проектов развития коммунальной и социальной инфраструктуры за счет использования механизмов государственно-частного партнерства и инструментов рынка ценных бумаг. Разработаны предложения по использованию геоинформационных систем для повышения привлекательности для инвестора объектов инфраструктуры, организации выпуска муниципальных ценных бумаг. Розглянуто питання фінансування проектів і програм розвитку інфраструктури великого промислового міста. Обґрунтовано необхідність розширення джерел фінансування проектів розвитку комунальної та соціальної інфраструктури за рахунок використання механізмів державно-приватного партнерства й інструментів ринку цінних паперів. Розроблено пропозиції щодо використання геоінформаційних систем для підвищення привабливості для інвестора об'єктів інфраструктури, організації випуску муніципальних цінних паперів. The paper examines the issues of financing projects and programs on the development of a large city’s infrastructure. Specific features of the infrastructure of a large city are determined. They are the heterogeneity and asymmetry of development. Therefore, the task of the city administration is to manage existing infrastructure facilities, build new facilities, and overcome the existing asymmetry at the expense of own and additionally attracted financial resources.The main sources of financing programs and projects on the development of a large city’s infrastructure are the funds of the state and local budgets, and extrabudgetary funds. At present, the funds of the state and local budgets are not sufficient enough to provide financing in full. So, it is necessary to attract extra-budgetary funds by using the mechanism of public-private partnership, securities market, deferred tax payments, etc. The grounds are given in favor of using the territorial community’s property to provide the attraction of investments by issuing municipal securities. An important reserve of financing infrastructure is the cooperation of local authorities and business structures on the principles of social partnership.The investment climate and investment attractiveness factors contribute to attracting business resources for implementing projects on infrastructure development. Factors of investment attractiveness include the information transparency and mutual loyalty of authorities and business. To provide the information transparency the geoinformation systems should be used that contain useful and reliable information about possible investees. The proposed approaches of attracting additional financial resources will improve financial security and implementation of projects and programs on the development of a large industrial city’s infrastructure.